BIOASSAY-GUIDED IDENTIFICATION OF CHEMICAL COMPONENTS IN TYPHONIUM ROXBURGHII SCHOTT - P, Annie Sulochana Selvakumari; A, John De Britto (Malaysian Journal of Science, 2011)
Typhonium roxburghii Schott (corm) extracts were screened for insecticidal activity against the storage pest Tribolium castaneum (Herbst). Among the different extracts tested, the benzene extract was found to be more effective (LC50 3.042% in 24 h). However, the yellow viscous mass obtained from the petroleum ether fraction of the benzene extract induced absolute mortality at 0.12% concentration (LC50 0.056% in 24 h). It was subjected to GC-MS studies and the chemical constituents were identified as methyl ester of 2-hydroxy benzoic acid, diethyl phthalate and dioctyl phthalate. Cultivation of T. roxburghii is possible because it does not prefer natural habitat. It is quick growing and needs no fencing. It can be cultivated in wastelands with fewer expenses. The positive externalities due to cultivation of T. roxburghii would be in the form of scenic beauty of the region with its evergreen leaves, virtual absence of mosquitoes even though sewage water be used. Identification of chemical constituents in T. roxburghii is a pioneer work and a more extensive exploratory study might reveal more. This can be exploited as an ecofriendly bio-pesticide. (Keywords: Typhonium roxburghii, Tribolium castaneum, benzene extract, LC50 values, chemical constituents.)